Haiku / Dr Nur Ilianis Adnan - Adnan, Nur Ilianis (Academy of Language Studies, 2024)
Some times, I make Haiku to express how I feel. Expressing feelings using Haiku makes me feel a lot better . I feel like I can remain calm and mysterious at the same time . A part from expressing my emotions, creating Haiku is also good for your brain. It trains your brain to stop and reflect. Try it if you don’t believe me. Here are some Haikus I made a few months back when I felt I needed to be more appreciated .